Identification of a Novel EHBP1‐MET Fusion in an Intrahepatic Cholangiocarcinoma Responding to Crizotinib. (12th October 2020) - Yu, Yiyi; Liu, Qing; Li, Wei; Qu, Yueting; Zhang, Yihong; Liu, Tianshu
Abstract: As an aggressive tumor, intrahepatic cholangiocarcinoma (ICC) originates in the epithelium of the bile duct and has a poor prognosis. The therapeutic options for ICC are challenging and limited because of poor response to chemotherapy and the lack of targeted therapy. Here we report on a 41‐year‐old female patient with ICC with EHBP1 ‐ MET fusion and multiple intrahepatic metastases responding to crizotinib. Next‐generation sequencing–based tumor mutation profiling was performed on the tumor biopsy and circulating tumor DNA from plasma. A novel EHBP1 ‐ MET fusion was identified and confirmed by Sanger sequencing. Immunohistochemistry of biopsy sample also revealed c‐MET positivity. Subsequently, the patient started treatment with MET inhibitor crizotinib. Magnetic resonance imaging scan demonstrated a partial response for 8 months. To the best of our knowledge, this is the first clinical case report of a patient with MET ‐rearranged ICC successfully treated with crizotinib. This case suggests that crizotinib may be a promising treatment option for patients with ICC with MET fusion, warranting further clinical investigation. Key Points: To the authors' knowledge, this is the first reported case of EHBP1 ‐ MET fusion. This is also the first clinical case report of clinical benefit from crizotinib treatment in an intrahepatic cholangiocarcinoma (ICC) with MET fusion. MET fusion is rare in ICC, and inhibition of MET could be a viable option for ICC that warrants further clinical investigation. Abstract : This case report describes a patient with intrahepatic cholangiocarcinoma with EHBP1 ‐ MET fusion successfully treated with crizotinib.